Komunikasi Edukatif Melalui Media Sosial pada Karyawan PT. Bank Mandiri (PERSERO) Tbk Wealth Management Group (WMG) - Indrawan, Robby (Da'watuna: Journal of Communication and Islamic Broadcasting, 2025)
This research aims to explore educational communication practices carried out via social media among PT employees. Bank Mandiri (Persero) Tbk Wealth Management Group (WMG). With the increasingly rapid development of technology, social media has now become one of the main channels for disseminating information, including for educational and training purposes for employees. The main focus of this research is how the use of social media as an educational communication tool can increase the knowledge and skills of employees in the WMG environment. This research approach uses qualitative methods with in-depth interview techniques and observations related to the implementation of educational communication by Bank Mandiri management. Research findings show that social media such as Tiktok, Instagram, and LinkedIn are effectively used to convey educational material to employees. Overall, it is hoped that this research can provide insight for companies to maximize the use of social media as a means of educational communication in the banking sector.